Perception of dalits who entered civil service through reservation system in Nepal - Paudyal, Pritha (Journal of Management and Development Studies, 2022)
Historically, Dalits have been one of the most marginalized caste groups in Nepal. Always pushed to the fringes of society, deprived of opportunities to make their way out of caste-based hierarchy, Dalits have always been among the lower rungs of society. To eliminate such discriminations and ensure their adequate representation at least in civil service, the concept of reservation, or quota-based hiring was introduced. This exploratory study attempts to understand how Dalits who have entered the civil service through the reservation system perceive themselves as civil servants. As per the findings of this study, Dalits who have entered the government through reservation system feel isolated and perceive others see them as incapable and not trustworthy. They also feel there exists an indirect discrimination in society which is something that they have experienced all their life. The study confirmed that Dalits who enter the government civil service through reservation system aspire to receive more encouragement at work, as they perceive such thrust will nurture confidence and result in better performance, but their caste status seems to have created problems to realize their aspiration into reality.